Assessment of awareness among parents about dietary habits and its relation to oral health in children: a cross sectional study - Hugar, Shweta S.; Manapragada, Saatmika; Hugar, Shivayogi; Pattar, Vilas; Karvekar, Shruti; Sureshbabu, Abhirami (International Journal Of Community Medicine And Public Health, 2024)
Background: Dental caries is one of the most common infectious diseases which occurs during early childhood and continues to be major public problem. Establishing healthy dietary habits right from a very young age not only improves the oral health but is essential for a child’s growth and development. Since parents are the main caregivers and prime regulators of child’s dietary intake, they play an important role in shaping child’s oral hygiene habits. Hence it is necessary for them to be aware of the right nutrition, right oral hygiene modalities and frequent dental visits for the betterment of child’s overall health. Methods: A cross-sectional survey was conducted among parents of children visiting to Department of Paediatric and Preventive Dentistry KAHER’s KLE VK Institute of dental sciences, Belagavi. Subjects were selected according to inclusion criteria. This study was a cross-sectional questionnaire-based study conducted among parents about dietary habits and its relation to oral health in children. Results: This study shows the statistically significant results with effect among parents about awareness of dietary habits and its relation to oral health in children. Conclusions: With the results it can be concluded that children who had parents with low knowledge scores were more likely to experience caries and have poor oral hygiene.